Understanding the Effects of Price Discrimination on Digital Market Competition - Rahman, Abdul (Journal of Economics and Management, 2025)
This study examines the influence of price discrimination on digital market competition in Nepalese quickly growing e-commerce sector. The research utilizes secondary data derived from 50 price observations gathered from prominent Nepali online platforms, including "Daraz," "Sastodeal," and "Gyapu," in addition to published reports and academic studies. It employs descriptive statistics and correlation analysis. The findings indicate that the average price fluctuation among Nepalese platforms varied from 5% to 11%, signifying the increasing adoption of algorithm-driven personalized pricing. Statistical findings demonstrate a robust positive correlation (r = 0.69) between price discrimination and revenue growth on platforms in Nepal. Conversely, an inverse correlation (r = –0.58) suggests that elevated levels of price discrimination diminish competition in the digital market. The results indicate that while personalized pricing boosts immediate revenue for Nepali e-commerce companies, it could undermine consumer trust and enhance the market dominance of leading platforms. The study concludes that Nepal necessitates enhanced pricing transparency and regulatory oversight to ensure equitable competition and protect consumer welfare in digital markets.